Widespread chromatin context-dependencies of DNA double-strand break repair proteins - Vergara, Xabier; Manjón, Anna G.; de Haas, Marcel; Morris, Ben; Schep, Ruben; Leemans, Christ; Friskes, Anoek; Beijersbergen, Roderick L.; Sanders, Mathijs A.; Medema, René H.; van Steensel, Bas (Nature communications, 2024)
DNA double-strand breaks are repaired by multiple pathways, including non-homologous end-joining (NHEJ) and microhomology-mediated end-joining (MMEJ). The balance of these pathways is dependent on the local chromatin context, but the underlying mechanisms are poorly understood. By combining knockout screening with a dual MMEJ:NHEJ reporter inserted in 19 different chromatin environments, we identified dozens of DNA repair proteins that modulate pathway balance dependent on the local chromatin state. Proteins that favor NHEJ mostly synergize with euchromatin, while proteins that favor MMEJ generally synergize with distinct types of heterochromatin. Examples of the former are BRCA2 and POLL, and of the latter the FANC complex and ATM. Moreover, in a diversity of human cancer types, loss of several of these proteins alters the distribution of pathway-specific mutations between heterochromatin and euchromatin. Together, these results uncover a complex network of proteins that regulate MMEJ:NHEJ balance in a chromatin context-dependent manner. DNA double-strand breaks are repaired by multiple pathways. The balance of these pathways depends on the local chromatin context, but the underlying mechanisms are poorly understood. Here the authors uncover a network of proteins that regulate pathway balance in a chromatin context-dependent manner.